ISOLATION OF ACTINOMYCETES FROM THE SEDIMENTS OF PICHAVARAM MANGROVE FOREST, SOUTH INDIA AND ANALYSING THEIR ANTIBACTERIAL EFFICACY - M, AARTHI; D, KAMALANATHAN; V, BALAKRISHNAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of the present investigation is to isolate actinomycetes from the sediments of Pichavaram mangrove forest, South India, and to screen for their antibacterial efficiency. Methods: Actinomycetes were isolated by culturing the samples in Starch Casein Agar medium; they were screened primarily for their antibacterial efficiency against Gram-positive and Gram-negative bacterial organisms. Solvent extraction was done with 50% (percentage) ethyl acetate, crude extracts of actinomycetes were prepared at different concentrations using dimethyl sulfoxide and treated against the bacterial organisms. Antibacterial assay was done in Mueller–Hinton agar medium. Results: Thirteen actinomycetes were isolated; among them, four actinomycete isolates (Pichavaram mangrove actinomycete 2 [PMA2], PMA6, PMA9, and PMA13) exhibited antibacterial activity. Conclusion: Isolate PMA2 exhibited very strong antibacterial activity and isolate PMA13 is weakly active against the tested bacterial organisms.